Peran Guru Dalam Peningkatan Hasil Belajar Aqidah Akhlak Di Sma Islam 1 Surakarta - Mukhlis Fathurrohman, Luthfi Imam Suharto (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study aims to analyze the role of teachers in improving Aqidah Akhlak learning outcomes at SMA Islam 1 Surakarta. Using a qualitative approach and a case study method, data were collected through observations, in-depth interviews with Islamic Education teachers, and documentation of the learning process. Data analysis was conducted using the Miles and Huberman technique, which includes data reduction, data presentation, and conclusion drawing. The results indicate that teachers play a crucial role in guiding students’ understanding and internalization of Aqidah Akhlak values. About 62.1% of students rated teachers as very active in providing clear guidance, while 34.5% stated that teachers were sufficiently active but lacked depth in their explanations. Effective strategies to enhance learning outcomes include implementing practice-based learning, strengthening teachers' roles as role models, creating a conducive learning environment, and involving parents in the learning process. The implications of this study highlight the importance of developing more innovative and interactive teaching methods to facilitate students’ understanding and application of Aqidah Akhlak values in daily life. Furthermore, collaboration between schools and parents is essential to create a more supportive learning environment.